Turkey – The West: Exemplary Antagonism? - Vladimir A. Avatkov; Alina I. Sbitneva (Современная Европа)
The article examines the Western direction of Turkey's foreign policy and its relations with its three key actors: the United States, NATO and the EU. By its centenary, which Turkey is celebrating on 29th of October, 2023, Ankara seeks to approach the status of an independent supra-regional power. For a long time, Turkey has served as a "junior ally" of Washington, but in the era of the polycentricity’s construction, it has significantly changed its foreign policy priorities. Relations with the United States have moved from an "exemplary partnership" to the rank of an exemplary antagonism and the path to "united Europe" has turned out to be more problematic and not profitable for Ankara from the point of view of its national interests. The NATO bloc has lost its primary importance due to Turkey's development of its own military-industrial complex and growing contradictions with existing and potential members of the alliance. Nevertheless, the West still has a great influence on economic and other related fields affecting the well-being of Ankara. In this regard, building constructive relations with the West remains one of the tasks of Turkey's foreign policy. The authors conclude that under current circumstances the complete political sovereignty of Ankara and its separation from the West can only occur within the framework of the "independence through dependence" model since Turkey due to the lack of its own resources for crisis-free existence will need the support of other stronger world players, such as Russia and, for example, China.